PENGARUH SELF EFFICACY DAN MINAT BELAJAR TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV A SD NEGERI DAYA 1 - Alifa, Nur Octaviani; Alannasir, Wahyullah; Rahmawati, Rahmawati (ALENA : Journal of Elementary Education, 2024)
This research aims to (1) obtain information about the effect of self-efficacy on the learning outcomes of mathematics students of grade IV A SDN Daya 1 Makassar, (2) obtain information about the influence of learning interest on the learning outcomes of mathematics students of grade IV A SDN Daya 1 Makassar, (3) measure the effect of self-efficacy and interest in learning about the learning outcomes of mathematics students of grade IV A SDN Daya 1 Makassar City. This research uses a quantitative approach, with an expost facto type of research. The object of this research is a grade IV A student of SDN Daya I Makassar. Data sources in this research are observations, interviews, questionnaires, learning outcomes tests and documentation. The data in this research were analyzed using 2 stages, namely descriptive statistical analysis and inferential statistical analysis which are divided into prerequisite tests (normality and linearity tests), hypothesis tests (simple regression tests and multiple regression tests). Based on the results of the research showed that: (1) from the results of hypothesis testing with a simple linear regression test between self-efficacy variables to mathematics learning outcome variables T count value of 6,169 Table 2,059 was obtained with a significance level of 0,020 < 0,05 which means there is an influence of self- efficacy on the results of learning Mathematics students of grade IV A SDN Daya 1 Makassar City. (2) from the results of hypothesis testing with a simple linear regression test between the variables of learning interest and the variables of mathematics learning outcomes, T count value of 2.192> Table of 2,059 with a significance level of efficacy of 0,038 0,05 which means that there is an influence of limited interest in Mathematics learning outcomes of student of grade IV A SDN Daya 1 Makassar. (3) the test result with multiple linear regression tests between self-efficacy variables and learning interest variables on mathematics learning outcomes obtained F value 6,438> Fable 3,39 with significance levels 0,006 < 0,05 and the value of the coefficient determination value or R square value of 0,340. So, it can be concluded that there is a significant influence between self-efficacy and interest in learning on the mathematics learning outcomes of grade IV A SDN Daya 1 Makassar.